INFLUENCE MEDIATION OF ORGANIZATIONAL INNOVATION ON PERFORMANCE AT THE TIRTA DAROY DRINKING WATER COMPANY (PDAM)AND TIRTA MOUNTALA ACEH - Amelia Rahmi; Rita Febri Salsabilla (CV. Radja Publika, 2024)
The purpose of this study is to determine the influence of Human Capital, Environmental Uncertainty through organizational innovation on non-financial business performance at the Tirta Daroy Drinking Water Company (PDAM) in Banda Aceh. The object of this study is the influence of Human Capital, Environmental Uncertainty through organizational innovation on non-financial business performance. The number of samples in this study was 159 employees. Research data were collected through questionnaires and documentation. Hypothesis testing in this study is presented based on research objectives. The level of confidence used is 95%, so the level of precision or inaccuracy limit is (α) = 7% = 0.07. And produces a t-table value of 1.96.